Stacking of antimicrobial genes in potato transgenic plants confers increased resistance to bacterial and fungal pathogens - Rivero, Mercedes (2012)
Solanum tuberosum plants were transformed with three genetic constructions expressing the Nicotiana tabacum AP24 osmotine, Phyllomedusa sauvagii dermaseptin and Gallus gallus lysozyme, and with a double-transgene construction expressing the AP24 and lysozyme sequences. Re-transformation of dermaseptin-transformed plants with the AP24/lysozyme construction allowed selection of plants simultaneously expressing the three transgenes. Potato lines expressing individual transgenes or double- and triple-transgene combinations were assayed for resistance to Erwinia carotovora using whole-plant and tuber infection assays. Resistance levels for both infection tests compared consistently for most potato lines and allowed selection of highly resistant phenotypes. Higher resistance levels were found in lines carrying the dermaseptin and lysozyme sequences, indicating that theses proteins are the major contributors to antibacterial activity. Similar results were obtained in tuber infection tests conducted with Streptomyces scabies. Plant lines showing the higher resistance to bacterial infections were challenged with Phytophthora infestans, Rhizoctonia solani and Fusarium solani. Considerable levels of resistance to each of these pathogens were evidenced employing semi-quantitative tests based in detached-leaf inoculation, fungal growth inhibition and in vitro plant inoculation. On the basis of these results, we propose that stacking of these transgenes is a promising approach to achieve resistance to both bacterial and fungal pathogens.